1993
DOI: 10.1111/j.1476-5381.1993.tb13928.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired sensory‐motor nerve function in the isolated mesenteric arterial bed of streptozotocin‐diabetic and ganglioside‐treated streptozotocin‐diabetic rats

Abstract: 1 Adult male Wistar rats were treated with streptozotocin (65 mg kg-', i.p.) to induce diabetes.Subgroups of age-matched control and streptozotocin-treated rats were given daily injections of mixed brain bovine gangliosides (60 mg kg' body weight, i.p.). At eight weeks after treatment mesenteric arterial beds from rats in each of the four groups were isolated and perfused and the function of perivascular nerves (sympathetic and sensory-motor), endothelium and smooth muscle was assessed. 2 Values for basal ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…Sensory nerve-mediated vasodilation of the perfused isolated mesenteric arterial bed has been reported to be reduced in rats 8 wk after induction of diabetes with STZ (28). However, in the present study, we observed no changes in the peptidergic innervation of either MAs or PMAs.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Sensory nerve-mediated vasodilation of the perfused isolated mesenteric arterial bed has been reported to be reduced in rats 8 wk after induction of diabetes with STZ (28). However, in the present study, we observed no changes in the peptidergic innervation of either MAs or PMAs.…”
Section: Discussioncontrasting
confidence: 55%
“…In tail artery, Hart et al (11) reported that 8 wk of diabetes produced a small reduction in sympathetic nerve-mediated vasoconstriction, whereas Weber and MacLeod (42) and Speirs et al (32) reported that 12 wk of diabetes did not reduce sympathetic nerve-mediated vasoconstriction. In the perfused mesenteric arterial bed, diabetes reduced sympathetic nerve-mediated pressor responses after 12 wk of diabetes (27), but this effect was not present after 8 wk (28). In mesenteric arteries, it is not known if the decrease in the sympathetic nerve-mediated pressor response produced by diabetes is associated with degeneration of the sympathetic nerve supply, but in tail artery the perivascular sympathetic innervation is not affected by 12 wk of diabetes (32).…”
mentioning
confidence: 81%
“…Virgin females and 21-day pregnant rats (term, 22 days) were killed by carbon dioxide asphyxiation. Mesenteric arterial beds were isolated and set up for perfusion by the method of McGregor (1966) essentially as described previously (Ralevic et al, 1993). The abdomen was opened and the superior mesenteric artery exposed and cannulated with a hypodermic needle.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenteric beds were isolated from the rats and set up for perfusion as described previously (Ralevic et al, 1993). The abdomen was opened and the superior mesenteric artery exposed and cannulated with a hypodermic needle.…”
Section: Isolated Mesenteric Arterial Bed Preparationmentioning
confidence: 99%